How do you measure the performance and effectiveness of web marketing? - Sterne, Jim (Henry Stewart Talks, 2009)
Legacy metrics, A short history of web analytics, Server capacity, Server logs, Data, Marketing optimization metrics, Measuring what you don't control, Reputation management, Competitive analysis, Web metrics potential, Customer data potential, Extending web analytics to marketing optimization, Using web data to manage the business
Archived at 2022/04/11